INCREDIBLE !NDIA CAMPAIGN : Destination Marketing and the role of Social Media - Bafna, Sanjana (2015)
Tourism is an important aspect of a country's domestic economy and helps in generating  valuable  employment  and  foreign  exchange.  Tourists  get  attracted  to  a particular  destination  because  they  are  excited  about  the  destination  and because there are no safety concerns about the destination. Destination branding is a concept that  encompasses  the  enhancement  of  the  'image'  tourists  have  about  a  particular destination.  This  research  explores  the  destination  branding  effort  of  India  i.e. Incredible  India.  It was  discovered  that  the  campaign  has  been  successful in  one  of the aspects of destination branding ‐ removal of the safety concerns of global tourists. The campaign has also been successful in attracting more tourists on a absolute basis. A relative study of the campaign compared to other campaigns shows that there is a need  of  increase  in  the  social  media  use  of  the  campaign  to  connect  to  the  next generation of  tourists. The  campaign  needs  to expand its  depth and width  of  social media  usage  to  be  of  more  impact  in  the  coming  years.  There  is  also  a  need  for  a unified theme  and  de‐centralized  control  so  that  more  aspects  of India  such  as medical  tourism  are  included.  Possible  ways  of  doing  the  same  are  by  province branding  and/or  city  branding  which  are  aligned  with  the  central  Incredible  India campaign.